Women's magazines in English from 1920 to 1972 instruments of American Hegemony - Encanto, Georgina R. (2004)
Using Gramsci's theory of hegemony, this paper discusses how women's magazines in English, specifically those that were published from 1920 to 1972, served as tools for the subjugation and cooptation of Filipino women towards accepting American colonial rule, and consequently, the ideologies of capitalism and patriarchy. While these magazines did show, during the early years of American colonization, some potential for advancing the feminist cause, they, on the whole, affirmed the dominant patriarchal and capitalist beliefs, values, and way of life in their covers, editorial contents and advertisements.